Do multiple body modifications alter pain threshold? - Yamamotová, Anna; Hrabák, Pavel; Hříbek, Petr; Rokyta, Richard (Physiological research, 2017)
In recent years, epidemiological data has shown an increasing number of young people who deliberately self-injure. There have also been parallel increases in the number of people with tattoos and those who voluntarily undergo painful procedures associated with piercing, scarification, and tattooing. People with self-injury behaviors often say that they do not feel the pain. However, there is no information regarding pain perception in those that visit tattoo parlors and piercing studios compared to those who don't. The aim of this study was to compare nociceptive sensitivity in four groups of subjects (n=105, mean age 26 years, 48 women and 57 men) with different motivations to experience pain (i.e., with and without multiple body modifications) in two different situations; (1) in controlled, emotionally neutral conditions, and (2) at a "Hell Party" (HP), an event organized by a piercing and tattoo parlor, with a main event featuring a public demonstration of painful techniques (burn scars, hanging on hooks, etc.). Pain thresholds of the fingers of the hand were measured using a thermal stimulator and mechanical algometer. In HP participants, information about alcohol intake, self-harming behavior, and psychiatric history were used in the analysis as intervening variables. Individuals with body modifications as well as without body modifications had higher thermal pain thresholds at Hell Party, compared to thresholds measured at control neutral conditions. No such differences were found relative to mechanical pain thresholds. Increased pain threshold in all HP participants, irrespectively of body modification, cannot be simply explained by a decrease in the sensory component of pain; instead, we found that the environment significantly influenced the cognitive and affective component of pain.
Keywords: vysoká teplota; Adolescent; Adult; Male; lidé; Humans; Pain Threshold; piercing; Young Adult; měření bolesti; Tattooing; Hot Temperature; mužské pohlaví; Body Piercing; dospělí; mladý dospělý; práh bolesti; ženské pohlaví; mladiství; Female; Pain Measurement; tetování